Molecular mechanisms of the induction of IL-12 and its inhibition by IL- 10 - Aste-Amezaga, Miguel; Ma, Xiaojing; Sartori, Alexandrina [UNESP]; Trinchieri, Giorgio (My University, 1998)
Exogenously added IL-10 rapidly inhibited Staphylococcus aureus- or LPS- induced cytokine mRNA expression in human PBMCs and monocytes, with a maximal effect observed when IL-10 was added from 20 h before until 1 h after the addition of the inducers. Nuclear run-on assays revealed that the inhibition of IL-12 p40, IL-12 p35, and TNF-α was at the gene transcriptional level and that the addition of IL-10 to S. aureus- or LPS-treated PBMCs did not affect mRNA stability. The inhibitory activity of IL-10 was abrogated by cycloheximide (CHX), suggesting the involvement of a newly synthesized protein(s). The addition of CHX at 2 h before S. aureus or LPS also inhibited the accumulation of IL-12 p40 mRNA, but did not inhibit IL-12 p35 and TNF-α mRNA. This finding suggests that p40 transcription is regulated through a de novo synthesized protein factor(s), whereas the addition of CHX at 2 h after S. aureus activation caused superinduction of the IL-12 p40, IL-12 p35, and TNF-α genes. These results indicate that in human monocytes, the mechanism(s) of IL-10 suppression of both IL-12 p40 and IL-12 p35 genes is primarily seen at the transcriptional level, and that the induction of the IL-12 p40 and p35 genes have different requirements for de novo protein synthesis.
Keywords: interleukin 10; interleukin 12; cellular immunity; controlled study; gene induction; genetic transcription; human; human cell; monocyte; mononuclear cell; priority journal; staphylococcus aureus; transcription regulation; Animals; CHO Cells; Cricetinae; Cycloheximide; Gene Expression Regulation; Humans; Interleukin-10; Interleukin-12; Kinetics; Lipopolysaccharides; Monocytes; Protein Synthesis Inhibitors; RNA, Messenger; Staphylococcus aureus; Time Factors; Transcription, Genetic; Tumor Necrosis Factor-alpha